An abundance of flowers : more great flower breeders of the past - Taylor, Judith M. (Swallow Press/Ohio University Press, 2018)
Walk into any nursery, florist, or supermarket, and you'll encounter displays of dozens of gorgeous flowers, from chrysanthemums to orchids. At one time these fanciful blooms were the rare trophies of the rich and influential--even the carnation, today thought of as one of the humblest cut flowers.